2010
DOI: 10.1182/blood.v116.21.5174.5174
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Physical Activity In Adult and Pediatric Patients with Thalassemia

Abstract: 5174 The U.S. Government's “2008 Physical Activity Guidelines for Americans” recommends children perform at least 60 minutes of moderate to vigorous intensity physical activities (PA) a day while the recommendation for adults is 30 minutes per day at least 5 days a week. As fewer Americans meet these guidelines, it is unknown where patients with thalassemia (Thal) stand. Based on anecdotal evidence, it is assumed that patients with Thal have decreased PA due to their severe anemia and cardiomyop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Poor physical fitness is a common feature among thalassemia patients. Several reports have shown that patients with thalassemia have lower mean scores of quality of life (QoL) than healthy subjects [ 18 , 19 ] and that especially the mean scores for physical activity were lower than scores of other dimensions [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor physical fitness is a common feature among thalassemia patients. Several reports have shown that patients with thalassemia have lower mean scores of quality of life (QoL) than healthy subjects [ 18 , 19 ] and that especially the mean scores for physical activity were lower than scores of other dimensions [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that thalassemia patients are less physically active and have significantly reduced muscle mass compared to the general population [ 19 ]. In our study, the filling of IPAQ questionnaire confirms that only a small percentage of them (27.8%) spend time in vigorous intensity activities and that moderate/vigorous PA is associated with best V’O 2 peak values.…”
Section: Discussionmentioning
confidence: 99%
“…There is no significant difference in the physical activity performed pre-transfusion and posttransfusion. 11 This can be caused by depression, 25 low levels of Hb in the long term, 26 the buildup of iron due to repeated blood transfusions and not taking iron-chelating drugs, 27 and pain resulting from bone marrow expansion and loss of bone mass. 28 Many factors can make BTM patients more susceptible to depression and low physical activity, including the impact of therapy and transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…10 Both pediatric and adult thalassemia sufferers spend more time with a sedentary lifestyle per day than their age group. 11 Thalassemia sufferers with depression experience decreased quality of life and almost two times the risk of limiting physical activity when compared to patients without depression. 3 Research conducted by Gariépy et al 11 stated that only 12.5% of thalassemia patients performed moderate and vigorous activity following the recommendations of the Physical Activity Guidelines.…”
Section: Introductionmentioning
confidence: 99%